2017
DOI: 10.1371/journal.pone.0182450
|View full text |Cite
|
Sign up to set email alerts
|

Onset of microglial entry into developing quail retina coincides with increased expression of active caspase-3 and is mediated by extracellular ATP and UDP

Abstract: Microglial cell precursors located in the area of the base of the pecten and the optic nerve head (BP/ONH) start to enter the retina of quail embryos at the 7th day of incubation (E7), subsequently colonizing the entire retina by central-to-peripheral tangential migration, as previously shown by our group. The present study demonstrates a precise chronological coincidence of the onset of microglial cell entry into the retina with a striking increase in death of retinal cells, as revealed by their active caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 95 publications
1
20
0
Order By: Relevance
“…Similar systems (cell‐type‐specific promoter driving bacterial NTR) have been used to ablate selected cell types in the zebrafish . Zebrafish microglia express mpeg1 ‐driven transgenes, and we confirmed that microglia in retinas of mpeg1 :nfsBeYFP zebrafish are YFP+ (Figure A,B), indicating that these microglial populations are susceptible to ablation by metronidazole (Mtz) treatment.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Similar systems (cell‐type‐specific promoter driving bacterial NTR) have been used to ablate selected cell types in the zebrafish . Zebrafish microglia express mpeg1 ‐driven transgenes, and we confirmed that microglia in retinas of mpeg1 :nfsBeYFP zebrafish are YFP+ (Figure A,B), indicating that these microglial populations are susceptible to ablation by metronidazole (Mtz) treatment.…”
Section: Resultssupporting
confidence: 70%
“…In the embryonic mouse retina, detection of microglia, the resident phagocytic macrophage population, coincides temporally with detection of cell death . In the zebrafish, apoptotic cells can be detected in the brain and retina by 2 days postfertilization, which is also coincident with colonization of the central nervous system (CNS) by microglia . In addition, using the zebrafish model organism, recent studies indicate that normal developmental apoptosis is a significant factor driving macrophage entry into and establishment of microglia in the brain …”
Section: Introductionmentioning
confidence: 99%
“…They are present in human retina by 10 weeks gestation and in mouse retina by E11.5, though it is likely they arrive even earlier [17, 18]. Similar timing has been documented in other species (E7 in quail, [19]; and at E12 in rat, [20]). Two waves of retinal microglia infiltration have been proposed based on the spatiotemporal localization of these cells.…”
Section: Main Textmentioning
confidence: 66%
“…These immunofluorescence results indicated cleaved caspase-3 expressed occasionally in normal retinal tissues in the developing stage [37,[40][41][42]. In the control group after transportation, cups of 30 days and 60 days manifested a remarkably higher number of apoptotic cells.…”
Section: Bam15 Protects Neuronal Intactness During Transportationmentioning
confidence: 68%